An audio steganography technique to maximize data hiding capacity along with least modification of host - Ab. Rahim, L.B. (Springer Verlag, 2014)
Steganography is the concept of concealing information within a cover media. In this paper, we present a technique to hide the text information within an audio file using a higher Least Significant Bit (LSB) layer. To hide text information within the audio file, we propose an approach that uses two LSB layers of the host file. The data hiding is done by minimum modification to the host file, which implies that changes of host audio file do not impact the Human Auditory System (HAS). Hiding of dual bit in the 4th and 1 st LSB layer improves the hiding cap acity of the host file. The proposed approach is also robust with respect to the errors, occurred during embedding of text in the audio files, as minimum modifications are performed on the original host audio. Â© Springer Science+Business Media Singapore 2014.